2020
DOI: 10.1002/advs.202001936
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Human Gut Microbiome in Chronic Kidney Disease

Abstract: Gut microbiota make up the largest microecosystem in the human body and are closely related to chronic metabolic diseases. Herein, 520 fecal samples are collected from different regions of China, the gut microbiome in chronic kidney disease (CKD) is characterized, and CKD classifiers based on microbial markers are constructed. Compared with healthy controls (HC, n = 210), gut microbial diversity is significantly decreased in CKD (n = 110), and the microbial community is remarkably distinguished from HC. Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
115
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(130 citation statements)
references
References 47 publications
8
115
3
4
Order By: Relevance
“…Twelve (12/25) studies analyzed the relatively distinct taxa at the phylum level ( Table S6 ), of which two studies (2/10) focused on ESRD [ 24 , 25 ]. Six (6/10) and three (3/10) studies demonstrated that Proteobacteria [ 24 , 25 , 27–29 , 33 ] and Fusobacteria [ 18 , 27 , 34 ] were more abundant, while two (2/10) studies [ 18 , 29 ] showed that the abundance of Synergistetes in patients with CKD was less than that in controls. The abundance of Firmicutes , Bacteroidetes , and Actinobacteria in patients with CKD was inconsistent when compared to controls.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve (12/25) studies analyzed the relatively distinct taxa at the phylum level ( Table S6 ), of which two studies (2/10) focused on ESRD [ 24 , 25 ]. Six (6/10) and three (3/10) studies demonstrated that Proteobacteria [ 24 , 25 , 27–29 , 33 ] and Fusobacteria [ 18 , 27 , 34 ] were more abundant, while two (2/10) studies [ 18 , 29 ] showed that the abundance of Synergistetes in patients with CKD was less than that in controls. The abundance of Firmicutes , Bacteroidetes , and Actinobacteria in patients with CKD was inconsistent when compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…Of 12 studies, 10 studies were conducted in China, and two (2/10) studies focused on ESRD. Five (5/8), two (2/8), and two (2/8) studies demonstrated that Proteobacteria [ 20 , 27–29 , 33 ], Fusobacteria [ 18 , 27 ], and Bacteroidetes [ 17 , 33 ] were more abundant, while four (4/8) and two (2/8) studies revealed that Firmicutes [ 17 , 27 , 28 , 33 ] and Synergistetes [ 18 , 29 ] were less abundant in Chinese CKD patients compared with healthy controls, respectively. However, the two studies conducted in the US [ 34 ] and Italy [ 19 ] did not identify any taxa with the same alteration in CKD patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations